The Influence of Green Tax Regulations on New Renewable Energy Funding in Indonesia - Leonard, Tommy; Heriyanti, Heriyanti; Pakpahan, Elvira Fitriyani; Fenitra, Rakotoarisoa Maminirina (BESTUUR, 2023)
Reen taxes, such as carbon taxes, can help countries invest in the latest technologies and achieve sustainable prosperity by funding renewable energy. However, we see that the current tax system still needs to be improved. This research aims to analyze the Influence of Green Tax Regulations on New Renewable Energy Funding in Indonesia. This research employs a normative legal approach informed by a literature review. The research results show that the various regulations regarding green tax regulations impact the non-maximization of new renewable energy funding. Taxes can generate government revenue by trading carbon credits to reduce greenhouse gas emissions. Additional funds can be used to fund initiatives in alternative settings. Green taxes, such as carbon taxes, can help countries invest in emerging technologies and achieve sustainable prosperity by providing funding for renewable energy.